Developing enterprise sponsored virtual communities: the case of a sme’s knowledge community - Soares, António Lucas (2021)
Part of this paper result from research work financed by the Fundação para a Ciência e Tecnologia - MCTES - POCTI/GES/49202 COLL-CT-2004-500276 KNOW-CONSTRUCT Internet Platform for Knowledge-based Customer Needs Management and Collaboration among SMEs (2005-2007). Project co-funded by the European Community. "Horizontal Research Activities Involving SMEs-Collective Research Programme.